The Influence of Net Interest Margin, Capital, Adequacy Ratio, Non-Performing Loan, Return on Equity, Loan to Deposit Ratio, and Underwriter to the Level of IPO Underpricing and Long Term Performance (Case Study: Banking Stock Period 2003-2013) - Putra, Mohammad Rimba; Anggono, Achmad Herlanto (Journal of Business and Management, 2013)
Banking sector that have been hit hard during both financial crisis is under the supervision of Indonesia Central Bank (Bank Indonesia) that regulates and supervise bank activities. One of the venues for bank to ensure their efficiency and to find new funds is through Initial Public Offering (IPO). Initial Public Offering is conducted by a company in order to register their shares toward capital market. The number of samples used for this study consists of 16 banks that conduct the IPO during the period of 2003-2013. For long term return which is after three year return with the Holding Period Return, the samples that are used consist of 10 banks from the sample of IPO from the year of 2003-2012. The hypotheses of this study were tested by using multiple regression test after conduct a preliminary test that consist of test of linearity, normality test, autocorrelation test, heteroscedasticity test, and multicolleniarity test. The result of the research showed that from the entire variables tested for IPO, there are no variables that provide significant effect on the initial return during the IPO (p-value bigger ≤ 0.05). For long term return, after elimination of one of the least significance variable (Loan to Deposit Ratio) it is found out that Return on Equity provide a significant effect toward the long term return. After elimination of the least significant variable, it is also found out that the whole variables provide a simultaneous influence toward the regression model (F test). Keywords: Stocks, IPO, Underpricing, Long Term Return, Net Interest Margin, Capital Adequacy Ratio, Non-Performing Loan, Return On Equity, Loan To Deposit Ratio, Underwriter ----------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.